A guided tour through quadratic hedging approaches - Martin Schweizer (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
This paper gives an overview of results and developments in the area of pricing and hedging contingent claims in an incomplete market by means of a quadratic criterion. We first present the approach of risk-minimization in the case where the underlying discounted price process X is a local martingale. We then discuss the extension to local risk-minimization when X is a semimartingale and explain the relations to the Föllmer-Schweizer decomposition and the minimal martingale measure. Finally we study mean-variance hedging, the variance-optimal martingale measure and the connections to closeness properties of spaces of stochastic integrals.
urn:nbn:de:kobv:11-10047021
Keywords: G10; C60; 330; risk-minimization; locally risk-minimizing; mean-variance hedging; minimal martingale measure; variance-optimal martingale measure; Föllmer-Schweizer decomposition; quadratic hedging criteria; incomplete markets